Constructing professional identities: the role of school climate in early-career university teachers - Erguvan Uras Eren; Derin Atay (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract Teacher professional identity is a complex and multifaceted phenomenon shaped by socio-cultural and institutional contexts, yet it remains underexplored in university settings. This study investigates how early-career teachers in two Turkish foundation universities construct their professional identities in response to the school climate over an academic year. Employing a qualitative design, data were collected through in-depth interviews and reflective essays conducted over an academic year and analyzed using the constant comparative method. Findings reveal that supportive school climate elements, such as a collaborative academic community, enhance professional identity formation, while negative institutional factors hinder development and contribute to novice teacher attrition. This study highlights the relationship between professional identity and school climate, offering insights for policymakers and educators to strengthen identity formation among early-career teachers. The findings emphasize the critical role of institutional support in addressing broader educational challenges, including teacher retention and instructional quality.